2016
DOI: 10.1183/13993003.01824-2015
|View full text |Cite
|
Sign up to set email alerts
|

Circulating desmosine levels do not predict emphysema progression but are associated with cardiovascular risk and mortality in COPD

Abstract: Elastin degradation is a key feature of emphysema and may have a role in the pathogenesis of atherosclerosis associated with chronic obstructive pulmonary disease (COPD). Circulating desmosine is a specific biomarker of elastin degradation. We investigated the association between plasma desmosine (pDES) and emphysema severity/progression, coronary artery calcium score (CACS) and mortality.pDES was measured in 1177 COPD patients and 110 healthy control subjects from two independent cohorts. Emphysema was assess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

11
83
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 69 publications
(95 citation statements)
references
References 37 publications
(49 reference statements)
11
83
0
1
Order By: Relevance
“…An increase in elastolysis may be due to either increases in elastolytic enzyme activity or reductions in inhibitors of these enzymes with subsequent replacement of elastin with collagen [24]. The findings of RABINOVICH et al [9] help us, as both scientists and clinicians, to understand further the possible mechanism of COPD and cardiovascular disease. They have shown that an increased level of elastolysis, by measuring plasma desmosine as a biomarker of elastin breakdown, exists in patients with COPD, in contrast to sex-and age-matched controls.…”
mentioning
confidence: 92%
See 4 more Smart Citations
“…An increase in elastolysis may be due to either increases in elastolytic enzyme activity or reductions in inhibitors of these enzymes with subsequent replacement of elastin with collagen [24]. The findings of RABINOVICH et al [9] help us, as both scientists and clinicians, to understand further the possible mechanism of COPD and cardiovascular disease. They have shown that an increased level of elastolysis, by measuring plasma desmosine as a biomarker of elastin breakdown, exists in patients with COPD, in contrast to sex-and age-matched controls.…”
mentioning
confidence: 92%
“…The lack of any association of plasma desmosine with emphysema or airflow obstruction is in contrast to that found previously [25], but is likely to reflect differences in the population studied, the size of the COPD population studied and possible differences in the definition of emphysema. Most significantly, the authors found an association with all-cause mortality and plasma desmosine levels in the COPD patient population [9]; however, without a control population with only cardiovascular disease it remains unclear if this is a COPD or cardiovascular phenomenon and warrants further investigation. This work [9] does further the hypothesis that the common factor in any association of COPD and cardiovascular risk is elastin loss.…”
mentioning
confidence: 99%
See 3 more Smart Citations